Constructing the ‘Responsible Tourist’: An Exploration of Identity and Self-Other Relations in the Online Texts of Niche and Mainstream Tour Operators - Ingram, Claire (2013)
This research explores how niche and mainstream tour operators frame the ‘responsible tourist’ within their online texts. Attention is paid to the manner in which tour operators contextualise the responsible tourism experience, construct the responsible tourist identity, and relate the responsible tourist (i.e. ‘self’’) to the ‘other’. Consequently, it is suggested that this project contributes to literary ‘gaps’ within the corporate social responsibility (CSR), consumer social responsibility (CnSR) and tourism literature in three primary ways. Firstly, by refuting the positivist assumption that the responsible tourist is functionally categorised according to consumer attributes, motivations, and subsequent responsible behaviours, this project (instead) interpretively develops how responsible tourists are negotiated via language. Secondly, by analysing language-use in websites, this study recognises the under-researched, yet influencing role of tour operators in constructing and positioning, as opposed to merely segmenting, the responsible tourist within corporate discourse. Thirdly, by analysing the texts of a ‘spectrum’ of niche to mainstream tour operators, this research not only addresses the deficient attention paid to the mass responsible tourist, but examines how corporate constructions vary across the two extreme modes of holiday experience. To conduct the research, discourse analysis was applied to the online texts of Tribes, Responsible Travel and Thomas Cook. Across the three texts, findings suggest that responsible tourism is contextualised (at the meso level) via three primary interpretative repertoires (safeguarding, mindful citizenship and authentic discovery) - leading to the corresponding subject positions of safe-guarder, mindful citizen and authentic discoverer. When expanded at the micro level, the subject positions convey the responsible tourist as a respectful protectionist and preservationist, who is not only aware of their potential to adversely impact the (dissimilar) environmental and socio-cultural traditions of the touree, but who resultantly gains extra from authentic interaction with the ‘other’ (i.e. ‘destination objects’ and ‘societal objects’ of responsibility). In this regard, the responsible ‘self’ is related to the ‘other’ through the rhetoric of benefits and differences. Overall, whilst the subject positions are relatively static across the three texts, it is noted that the explicitness (i.e. regarding the types and extent) of objects, benefits and differences noticeably varies. This project is of use to academics interested in the role of tour operators in constructing the responsible tourist across the niche to mainstream spectrum, as well as practitioners, who, given the increased demand for responsible holidays, similarly wish to discern how the ostensibly responsible tourist is negotiated, and related to the ‘other’, across different modes of tourism.